Simulating the implications of oxide scale formations in austenitic steels of ultra-supercritical fossil power plants - Yeo W.H.; Fry A.T.; Ramesh S.; Mohan R.; Liew H.L.; Inayat-Hussain J.I.; Purbolaksono J. (Elsevier Ltd, 2023)
Formation of steam-side oxide scale that can cause major failures in boilers is a large concern in fossil-fueled power plant operation. In this work, we attempt to simulate the implications of oxide scale formation and subsequently assumed exfoliation in the given length of an austenitic tube of ultra-supercritical (USC) fossil power plants under different presumed service conditions. The incremental procedures used to determine the average metal temperature and scale thickness over a period of time in superheater/reheater tubes at a specified steam temperature are presented. A number of simulation results for both formation and subsequent exfoliation of the oxide scales are presented and discussed. Based on the simulation results, the estimated scale growth and presumed exfoliation rate in austenitic steels at 650. °C seemed to be allowable. However, to run USC power plants with steam condition of around 650. °C, more detailed studies are required. © 2014 Elsevier Ltd.